GCSE success AQA maths linear higher workbook - "Mapp, Fiona C." (Letts London, 2007)
Suitable for the AQA exam board, this title offers content to help students manage their revision and prepare for exams. It is broken into manageable sections and offers advice to help build students' confidence. It offers exam tips and techniques to support students throughout the revision process. For 2010/2011 exams only.